Comparison of NEWS2 and CURB65 Score in Predicting Mortality of Hospitalized patients with AECOPD - Neelam Kumari, Aneel Kumar, Raniyah Akhter, Nausheen Saifullah, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the diagnostic accuracy of the NEWS2 and CURB-65 scores in predicting in-hospital mortality in patients with acute exacerbations of COPD, mortality during hospital stays is considered the gold standard. Study Design: Cross-sectional study-design. Place and duration of study: Department of Chest Medicine, JPMC, Karachi, from September 25, 2020, to January 25, 2021. Two hundred and twelve patients of both genders were included who were admitted because of acute COPD exacerbations. The National Early Warning Score 2 (NEWS2) and CURB-65 Score in the estimation and evaluation of hospital-related mortality were noted. Results: NEWS2 predicted 156(73.6%), CURB-65 predicted 72(34%) as high-risk patients, and in-hospital mortality was 39(18.4%). NEWS2 had shown sensitivity of 100%, specificity of 32.4%, diagnostic accuracy of 45%, PPV of 25.1%, and NPV of 100% as a prediction value of in-hospital mortality. CURB-65 had shown sensitivity of 76.9%, specificity of 75.7%, and diagnostic accuracy of 76%, PPV of 41.7%, and NPV of 93.6% as a prediction value of in-hospital mortality. Implication: It is recommended that individual analyses of these associated factors be performed in future studies for the formulation of novel, efficient scores that may be better predictors of mortality in AECOPD patients. Conclusion: Both of the scoring systems can be used for the purpose of AECOPD patients risk stratification as per clinicians’ preference and as the basic tools of assessment in a resource-poor country. Keywords: Acute exacerbation of COPD, NEWS2, CURB-65, In-hospital mortality